Cure Behaviour Study of Phenol Formaldehyde on Wood Surface Using Micro-Thermal Analysis - Anbu Johnson, Dr.; Ragunathan Santiagoo; Ning Yan (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.